Alternative Views of Authenticity: The Case of Park Hill, Sheffield - Walter, Nigel (Protection of Cultural Heritage, 2025)
Park Hill is the largest listed building in Europe. Opened in 1961, its design is an innovation on Le Corbusier’s Unité d’Habitation, with horizontal ‘streets in the sky’ at every third level, with duplex apartments extending above and below each access level. It was Britain’s first completed scheme of post-war slum clearance and the most ambitious inner-city development of its time. However, while the development was conceived and opened with great optimism, by the time it was listed in 1998 it was in serious decline, both socially and physically. Unable to finance its refurbishment, Sheffield City Council sold Park Hill to developers for £1 in 2004. With the extensive involvement of Historic England, the subsequent refurbishment has upgraded the buildings and gentrified them, with only a small minority of units being available for affordable housing. The form and much of the physical fabric of the development has been preserved, but its original social significance has arguably been lost. This paper examines Park Hill in the context of the development of the notion of authenticity from the Venice Charter (1964) through to the Nara Document (1994). The paper concludes that the listing and protection of a building such as Park Hill would not have been possible without the development of the multivalent approach to authenticity in the Nara Document, which forms an essential aspect of the broadened understanding of what constitutes cultural heritage.